(untitled) (Fiep Bulletin - online, 2015)
With the aging process, people gradually loose the physical fitness levels and functional capacity. The regular physical activity may be an important element to try to maintain or reduce such losses, and, additionally, may assist in the prevention of certain diseases which are more liable of arising at old age. Thus, the object of this study was to trace a physical fitness profile of women over 81 years of age, which entered the "Senior Project For Active Life of USJT Universidade São Judas Tadeu" during the period 2002 to 2004. The elders participated of a physical fitness and functional capacity series of tests proposed by Matsudo 2004. The data were analyzed through descriptive statistics (average and standard deviation). The analysis of the results showed that, for the aerobic power, flexibility, agility and balance the group shows inferior fitness levels as compared to the literature. Only for the muscle strength tests, the group analyzed herein has proven to be more qualified. From such findings, we conclude that the elders of this study do not fully fit the regulations submitted for these tests, and show how important is the initial evaluation for the prescription of physical activity for conform to the aptitude level of the participants.